Boundary-less-Banking: Bankers’ Perception on Online-Banking in Meerut District - Saxena, Dr. P. K. (Journal of Commerce and Trade, 2017)
Online Banking in simple terms means, banking services through website which does not involve any physical exchange of money, but it’s all done electronically, from one account to another. There is no need to go to the bank for transactions. Instead, one can access one’s account any time and from any part of the world, and not necessarily at times when the bank is open. For busy executives, students, and homemakers, online-banking is like a virtual boon. No more taking precious time off from work to get a demand draft made or a Chequebook issued. Albeit, the day is not far enough when there will be any need for Demand Draft and cheque transactions and Pass book printing facilities. Banks use a variety of names for online banking services, such as PC banking, home banking, electronic banking, boundary less banking or Internet banking. The present study is done in Meerut district with a basic hypothesis that the Banks are not able to provide full benefits of the Online-Banking to all customers. Lack of education and lower per-day wages are two hard facts that drawback lower level Indian population from the usage of online-banking. On the other hand, Government and organisational environment are influencing the Indian Banking System to be more electronic-friendly so as to provide easyness in banking procedures. These two polar reversals forced the author to conduct a study entitled “Boundry-less-Banking : Banker’s perception on Online-Banking is Meerut District”. JEL Classification : G 21, O 16, P 43.